Diferentes doses de calagem no crescimento inicial de cultivares de tomates cereja em Humaitá-AM - Motter, Bruna da Silva (Brasil, 2025)
Vegetable production in the Brazilian Amazon faces limitations related to soil acidity and low fertility, which requires agricultural practices that improve growing conditions. This study aimed to evaluate the effect of different lime rates on the initial growth of two cherry tomato cultivars in a protected environment, under acidic soil conditions in the Amazon region. The experiment was conducted on the campus of the Federal University of Amazonas (UFAM), in Humaitá-AM, using a highly randomized design, in a 2 x 6 factorial scheme, with the first factor being two tomato cultivars (Yubi and Cereja Vermelho) and the second factor consisting of six lime rates (0, 1, 2, 4, 8 and 12 t ha-1), with three replicates. The soil, characterized by high acidity (pH 4.42) and low fertility, was collected in a forest area, treated with increasing lime rates, and incubated for 30 days before transplanting the seedlings. Plants were evaluated for height, number of leaves, stem diameter, dry biomass and chlorophyll index, using standard specificity for plant growth and development. The results indicated that lime application significantly improved soil pH and the availability of essential nutrients, promoting greater plant growth. Doses between 8 and 12 t/ha provided the best results in terms of biomass accumulation and photosynthetic activity, with the cultivar Cereja Vermelho showing superior performance in height and number of leaves.